Polychlorinated dibenzo-p-dioxins, polychlorinated dibenzofurans and polybrominated diphenyl ethers in sediments and fish species from the Murchison Bay of Lake Victoria, Uganda - Ssebugere, Patrick; Sillanpää, Mika; Wang, Pu; Li, Yingming; Kiremire, Bernard T.; Kasozi, Gabriel N.; Zhu, Chaofei; Ren, Daiwei; Shang, Hongtao; Zhang, Qinghua; Jiang, Guibin (Science of the total environment, 2014)
Polychlorinated dibenzo-p-dioxins/furans (PCDD/Fs) and polybrominated diphenyl ethers (PBDEs) were analyzed in sediments and fish from the Murchison Bay of Lake Victoria by high resolution gas chromatography/ high resolution mass spectrometry (HRGC/HRMS). Average concentrations of total (Σ) PCDD/Fs and ΣPBDEs in sediments ranged from 68.8 to 479 pg g−1 dry weight (dw) and 60.8 to 179 pg g−1 dw, respectively. Contamination levels of sedimentary PCDD/Fs and PBDEs were low to moderate compared to other urbanized regions worldwide. The concentrations in different fish species (Nile perch; Lates niloticus and Nile tilapia; Oreochromis niloticus) were 5.32 to 49.0 pg g−1 wet weight (ww) for PCDD/Fs and 59.3 to 495 pg g−1 ww for PBDEs. Higher concentrations of the pollutants were found in L. niloticus than O. niloticus, which could be attributed to species differences in feeding habits and lifestyles. World Health Organization-toxic equivalents (WHO2005-TEQs) for PCDD/Fs ranged from 0.08 to 0.33 pg TEQ g−1 dw and 0.001–0.14 pg TEQ g−1 ww in sediments and fish, respectively. The TEQ values were lowcompared to the data for fresh water fish reported in literature andwithin a permissible level of 3.5 pg g−1wwrecommended by the European Commission. Based on the Commission set value and minimum risk level criteria formulated by the Agency for Toxic Substances and Disease Registry, the fish from the Murchison Bay was fit for human consumption.
Keywords: PCDD/Fs; PBDEs; Sediments; Fish; Lake Victoria